KATA KERJA BANTU MODAL DALAM NASKAH FILM TED KARYA SETH MACFARLANE, ALEC SULKIN DAN WELLESLEY WILD - SHALEH, ARDI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This study is attempt to describe, clasify and analyze modal verb in The film script Ted by Seth Macfarlane , Alec Sulkin and Wellesley Wild. The auxiliary verb modals are auxiliary words that serve as "helping verbs" to get more meaning. The effect of tense of the modals is different from verb.  The writer uses descriptive method. The data of the modals are collected from the sentences found in the script. The theory of Robert is used in this research . They are pure modals, special modals, and semi modals. Pure modals are can, could, will, would, shall, should, may, might and must. Special modals which used are be going to, have to, had better, had rather, be to, be able to, and ought to. Semi modals which used are dare and need. The writer focus to analyze about pure modals. The meaning of modals auxiliaries in The film script Ted by Seth Macfarlane , Alec Sulkin and Wellesley Wild. The auxiliary verb modals are: Can means ability, permission, and suggestion. Could means ability, possibility, permission, suggestion, and request. May means request and possibility. Might means possibility and permission. Will means willingness, intention, and request. Would means willingness, certainty, intention , and offering. Shall means request. Should means obligation, possibility, necessity. Must means necessity, possibility, obligation, and request. Keywords : Modals Auxiliary Verb : Script, Ted by Seth Macfarlane , Alec Sulkin and                   Wellesley Wild : English : Skripsi